Mối quan hệ giữa tiết kiệm, vị thế tài sản nước ngoài ròng và sự biến động của tài khoản vãng lai - Nguyễn Thị Liên , Hoa; Lê Ngọc , Toàn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
By examining traditional and modern views both in isolation and in combination, this study performs an analysis of the relationships among savings, net foreign assets position, and fluctuations of current accounts using a sample of 44 developing and industrial countries during 1980–2013. While the traditional rules maintain that the effect of the current account is equal to the amount of savings created by transitory income shocks, the impact of transitory income shocks on current accounts, under the modern views, equal the amount of savings multiplied by net foreign assets position. In the event of moderate net foreign asset position, a combination of the two views is highly advocated. By comparing the two groups of countries, it can be observed that: (i) for industrial countries, the new rules dominate; and (ii) for developing countries, it is the traditional rules that matter, and there is a negative correlation between net assets and current accounts.